Enhancement of interfacial shear strength due to cooperative π-π interaction between polyphenylene sulfide and carbon fiber and molecular orientation of polyphenylene sulfide via the π-π interaction. (February 2023) - Uematsu, Hideyuki; Yoshida, Kou; Yamaguchi, Ayaka; Fukushima, Akinori; Sugihara, Shinji; Yamane, Masachika; Ozaki, Yukihiro; Tanoue, Shuichi
Abstract: Carbon fiber (CF) with different surface functional groups was composited with two types of polyphenylene sulfide (PPS), without a sizing agent. The shear strength of the interface between high-reactivity PPS and CF was smaller than that of low-reactivity PPS and CF. Micro-Raman spectroscopy investigation of the PPS structure at the interphase revealed that the orientation of the PPS chains in the axial direction of the reinforcing fibers via π-π interaction between the phenyl ring of the PPS backbone and the phenyl ring of CF, and these interaction and orientation of the chains cooperatively contribute to the interfacial adhesion strength. The π-π interaction was attenuated in the composite of PPS with high reactivity potential and CF with functional groups such as –OH and –COOH. Thus, it is revealed that acid modification of the CF surface and PPS is not absolutely necessary in CF with an inert surface, such as recycled CF.